Diffusion Limited Cryopreservation of Tissue with Radiofrequency Heated Metal Forms. Issue 19 (2nd September 2020) - Han, Zonghu; Sharma, Anirudh; Gao, Zhe; Carlson, Timothy W.; O'Sullivan, M. Gerard; Finger, Erik B.; Bischof, John C.
Abstract: Cryopreserved tissues are increasingly needed in biomedical applications. However, successful cryopreservation is generally only reported for thin tissues (≤1 mm). This work presents several innovations to reduce cryoprotectant (CPA) toxicity and improve tissue cryopreservation, including 1) improved tissue warming rates through radiofrequency metal form and field optimization and 2) an experimentally verified predictive model to optimize CPA loading and rewarming to reduce toxicity. CPA loading is studied by microcomputed tomography (µCT) imaging, rewarming by thermal measurements, and modeling, and viability is measured after loading and/or cryopreservation by alamarBlue and histology. Loading conditions for three common CPA cocktails (6, 8.4, and 9.3 m ) are designed, and then fast cooling and metal forms rewarming (up to 2000 °C min −1 ) achieve ≥90% viability in cryopreserved 1–2 mm arteries with various CPAs. Despite high viability by alamarBlue, histology shows subtle changes after cryopreservation suggesting some degree of cell damage especially in the central portions of thicker arteries up to 2 mm. While further studies are needed, these results show careful CPA loading and higher metal forms warming rates can help reduce CPA loading toxicity and improve outcomes from cryopreservation in tissues while also offering new protocols to preserve larger tissues ≥1 mm in thickness. Abstract : Thick tissues can be successfully cryopreserved and rewarmed with the help of ultra‐rapid metal form heating. The first case of successful cryopreservation and rewarming of 2 mm thick porcine aorta is theoretically predicted and experimentally achieved, and the model which is validated by the arterial tissue can also be applied to other tissue systems.